Risks of spontaneous injury and extraction of an active fixation pacemaker lead: report of the Accufix Multicenter Clinical Study and Worldwide Registry - Kay, G N; Brinker, J A; Kawanishi, D T; Love, C J; Lloyd, M A; Reeves, R C; Pioger, G; Fee, J A; Overland, M K; Ensign, L G; Grunkemeier, G L (Circulation (New York, N.Y.), 1999)
The Telectronics Accufix pacing leads were recalled in November 1994 after 2 deaths and 2 nonfatal injuries were reported. This multicenter clinical study (MCS) of patients with Accufix leads was designed to determine the rate of spontaneous injury related to the J retention wire and results of lead extraction. The MCS included 2589 patients with Accufix atrial pacing leads that were implanted at or who were followed up at 12 medical centers. Patients underwent cinefluoroscopic imaging of their lead every 6 months. The risk of J retention wire fracture was approximately 5.6%/y at 5 years and 4.7%/y at 10 years after implantation. The annual risk of protrusion was 1.5%. A total of 40 spontaneous injuries were reported to a worldwide registry (WWR) that included data from 34 672 patients (34 892 Accufix leads), including pericardial tamponade (n=19), pericardial effusion (n=5), atrial perforation (n=3), J retention wire embolization (n=4), and death (n=6). The risk of injury was 0.02%/y (95% CI, 0.0025 to 0. 072) in the MCS and 0.048%/y (95% CI, 0.035 to 0.067) in the WWR. A total of 5299 leads (13%) have been extracted worldwide. After recall in the WWR, fatal extraction complications occurred in 0.4% of intravascular procedures (16 of 4023), with life-threatening complications in 0.5% (n=21). Extraction complications increased with implant duration, female sex, and J retention wire protrusion. Accufix pacing leads pose a low, ongoing risk of injury. Extraction is associated with substantially higher risks, and a conservative management approach is indicated for most patients.